Prevalence and Factors Associated with Insomnia Among a Representative Sample of the Lebanese Population: Results of a Cross-Sectional Study - Gloria Al Karaki; Souheil Hallit; Diana Malaeb; Nelly Kheir; Hala Sacre; Pascale Salameh; Rabih Hallit (Springer, 2020)
The objectives of the study were to identify the prevalence of insomnia among a representative sample of the Lebanese population and to assess potential factors associated with insomnia among this group. A cross-sectional study was done in the Lebanese population from August 2017 to April 2018 enrolling 789 participants using a proportionate random sample from all five Lebanese governorates. Participants filled a self-administered Arabic questionnaire. The Athens Insomnia Scale was used to diagnose insomnia. The Hamilton Depression Rating Scale and the Generalized Anxiety Disorder Scale were used to measure depression and anxiety, respectively. The prevalence of insomnia was 47.1% in the population sampled. The mean age of the participants was 37 years (64% females). Death in the family [adjusted odds ratio (aORa) = 1.59], drinking caffeine before sleep more than 2 days per week compared to none (aORa = 1.57), increased stress (aORa = 1.03), increased depression (aORa = 1.14), and anxiety scores (aORa = 1.07) were associated with higher odds of insomnia. The prevalence of insomnia was very high in the Lebanese population, and it was mainly associated with modifiable, treatable risk factors. Improved knowledge and adequate screening for insomnia are needed to promote better sleep quality.